2001
DOI: 10.1002/1097-4636(20011205)57:3<336::aid-jbm1176>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface chemistry and adsorbed proteins on monocyte/macrophage adhesion to chemically modified polystyrene surfaces

Abstract: Monocytes and macrophages play critical roles in inflammatory responses to implanted biomaterials. Monocyte adhesion may lead to macrophage activation and the foreign body response. We report that surface chemistry, preadsorbed proteins, and adhesion time all play important roles during monocyte adhesion in vitro. The surface chemistry of tissue culture polystyrene (TCPS), polystyrene, Primaria, and ultra low attachment (ULA) used for adhesion studies was characterized by electron spectroscopy for chemical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(206 citation statements)
references
References 47 publications
8
196
1
1
Order By: Relevance
“…Recently it has been demonstrated in the literature that these effects can be expressed in the cell at the level of genomic regulation, thus contributing to very fundamental changes in cellular physiology, ultimately resulting in unknown adjustments to cellular proliferation, motility and, in some cases, phenotype [17][18][19][20][21][22][23]. In this work we have demonstrated that measurements of cellular proliferation and viability on coated spectroscopic substrates can be correlated with spectral changes induced by adjustments to cell physiology when cultured on the different coatings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has been demonstrated in the literature that these effects can be expressed in the cell at the level of genomic regulation, thus contributing to very fundamental changes in cellular physiology, ultimately resulting in unknown adjustments to cellular proliferation, motility and, in some cases, phenotype [17][18][19][20][21][22][23]. In this work we have demonstrated that measurements of cellular proliferation and viability on coated spectroscopic substrates can be correlated with spectral changes induced by adjustments to cell physiology when cultured on the different coatings.…”
Section: Resultsmentioning
confidence: 99%
“…This ultimately results in increasing proliferation and motility, which is also dependent on the charge distribution presented by the ECM coating molecule to the adhering cell [18][19][20][21][22][23]25]. Ultimately the reaction of the cell to such influences are complex, being the cumulative effect of the increased or decreased regulation of a number of stimulatory pathways in the cell, with the end physiological change in any given cell being dependent on the cell and substrate ECM [50,51].…”
Section: Fluorescence/absorbance Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in conformation expose sequences not normally accessible within the protein that can further interact with other proteins or indeed act as focal attachment points for cellular adhesion. 11 In the in vitro cell adhesion assays described here, various experimental protocols were examined to assess the effect of the presence of serum proteins. The overriding observation from the entire study was that in all assays performed, far fewer inflammatory cells adhered to the PC-coated samples compared with the uncoated controls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, monocyte adhesion on a poorly adhesive surface is enhanced by adsorbed IgG [6], while others have shown that fibrinogen is more critical for phagocyte adhesion on biomaterials [7]. Others and we have demonstrated that macrophage adhesion is mainly modulated by the substrate and the extracellular matrix protein such as fibronectin [8,9].…”
Section: Introductionmentioning
confidence: 99%